2006
DOI: 10.1007/s00508-006-0694-y
|View full text |Cite
|
Sign up to set email alerts
|

Paradigm Burgenland: Risk of Borrelia burgdorferi sensu lato infection indicated by variable seroprevalence rates in hunters

Abstract: We found an overall seroprevalence of 54% in asymptomatic hunters of Burgenland. Infectious risk exists in the entire state but the prevalence rate differs in the various districts indicating a variable risk which peaks in the south. The nearly linear increase of seroprevalence with age and duration of hunting activity reflects repeated tick exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 10 publications
2
23
0
1
Order By: Relevance
“…Since the mid-1980s, Austria has been recognised as an LB endemic area (Stanek et al, 1985(Stanek et al, , 1987(Stanek et al, , 1988Stu¨nzner et al, 1999) and, interestingly, a very recent Austrian study revealed a high seropositivity rate to B. burgdorferi s.l. (54%) among clinically asymptomatic Austrian hunters (n ¼ 1253) (Cetin et al, 2006). Although the sampling size was rather small, our study clearly confirms the risk of acquiring LB throughout Austria and, moreover, shows a clear trend concerning both the distribution of B. burgdorferi s.l.…”
Section: Discussionsupporting
confidence: 76%
“…Since the mid-1980s, Austria has been recognised as an LB endemic area (Stanek et al, 1985(Stanek et al, , 1987(Stanek et al, , 1988Stu¨nzner et al, 1999) and, interestingly, a very recent Austrian study revealed a high seropositivity rate to B. burgdorferi s.l. (54%) among clinically asymptomatic Austrian hunters (n ¼ 1253) (Cetin et al, 2006). Although the sampling size was rather small, our study clearly confirms the risk of acquiring LB throughout Austria and, moreover, shows a clear trend concerning both the distribution of B. burgdorferi s.l.…”
Section: Discussionsupporting
confidence: 76%
“…All this together may explain why the seroprevalence was higher among the participants from the Åland Islands compared to the participants from South Central Sweden and from Southernmost Sweden. The seroprevalence in the TBD STINGstudy (20%) is within the range of those reported from other Europe-an studies: in healthy blood donors the seroprevalence ranged between 2 and 24% (Ekerfelt et al, 2001;Fahrer et al, 1991a;Gustafson et al, 1993a;Hristea et al, 2001;Tjernberg et al, 2007;Tomao et al, 2005); in people living in endemic regions between 7 and 29% (Berglund & Eitrem, 1993;Carlsson et al, 1998;Gustafson et al, 1993b;Werner et al, 2001); and for people in high-risk groups (outdoor workers, orienteers and hunters) between 9 and 54% (Cetin et al, 2006;Fahrer et al, 1991a;Gustafson et al, 1993a;Hristea et al, 2001;Tomao et al, 2005).…”
Section: Are There Gender-and Geographical Differences In the Borrelisupporting
confidence: 59%
“…Most of the clinical symptoms described have a high prevalence in the general population and cannot be used to differentiate between LB and non-LB patients, as has been shown previously by Donta et al (10) and Seltzer et al (11). On the other hand, in an Austrian study, the seropositivity rate in the local population was up to 70%, depending on age and the risk of exposure to ticks (12). The seropositive individuals investigated did not have complaints compatible with chronic LB.…”
Section: Discussionmentioning
confidence: 66%